Kemaslahatan dalam Mahar Berupa Pengajaran Ilmu Duniawi: Kajian Maslahah Mursalah - Yusrizal, Navis (Institut Agama Islam Negeri Metro, 2024)
Article 31 of the Compilation of Islamic Law clearly regulates that the woman may lighten the mahr burden for the man in accordance with Islamic teachings. However, the reality in some ethnic groups in Indonesia, such as the Bugis, sets high mahr requirements that do not take into account the financial ability of the prospective husbands. In the Bugis culture, the mahr is adjusted based on the level of education of the prospective wife, with higher educational levels resulting in a higher mahr. As a result, the concept of mahr in the form of teaching worldly knowledge has become an alternative for marriage mahr. The purpose of this study is to understand the legal perspective on mahr in the form of teaching worldly knowledge and how maslahah mursalah views this type of mahr. This research uses a descriptive qualitative method with library research techniques, where the author gathers information from classical fiqh books, theses, and websites. After systematically analyzing the data, the author draws conclusions. The conclusion is that Imam Shafi'i and Imam Hanbali permit mahr in the form of a beneficial task whose benefits are clear, such as teaching the Qur'an, permissible poetry, literature, writing, handicrafts, and other beneficial and permissible activities. From the perspective of maslahah mursalah, mahr in the form of teaching worldly knowledge brings maslahah for the wife in her life. Moreover, if the knowledge taught involves skills needed in the present day, such as programming, editing, filming, and so on, it will result in financial income that can support the wife’s financial needs in her daily life.